USER’S OPINIONS ON ANDROID-BASED LEARNING - Marko Ayaki Lumbantobing; Muhammad Hudan Rahmat (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2019)
The purpose of this research is to find out the user's response to e-module based on android products to facilitate learning process. Likert scale with four variations of the answer was the scale used in this study. Research data were analyzed by quantitative descriptive. The result of the research showed that e-module based on android products have met the eligibility criteria with the category